An Analysis of Figurative Language in Live Sports Commentary: A Study of Karate Competitions - Galuh Wuryaningtyas; Markus Budiraharjo (International Journal of English Linguistics, Literature, and Education (IJELLE), 2025)
Live sports commentary plays a crucial role in enhancing the audience’s experience by covering sporting events' excitement, atmosphere, and emotional intensity. Commentators use various linguistic devices, including figurative language, specialized lexicons, jargon, and registers, to create vivid and engaging narratives. This study investigates the types of figurative language commonly used in live karate commentary. Using a qualitative approach, the study analyzed 10 transcripts of live commentaries from the Tokyo Karate1-Premier League 2019 event. The data were categorized based on different types of figurative language identified in the commentary. The finding revealed that commentators utilized nine figurative language types: metaphor (27.4%), hyperbole (21.7%), personification (20.8%), synecdoche (6.6%), irony (6.6%), paradox (5.7%), understatement (5.7%), simile (3.8%), and metonymy (1.9%). In total, 106 data were obtained from various figurative language used by the commentators. These linguistic elements enriched the commentary by adding depth, excitement, and expressiveness to the descriptions of karate matches. Figurative language helped emphasize techniques, strategies, and dramatic moments, making the commentary more engaging for the audience. This research contributes to a deeper comprehension of the literary devices that shape sports narratives by elaborating on the various figurative language used in karate live commentary.